2022
DOI: 10.1177/10775463211068905
|View full text |Cite
|
Sign up to set email alerts
|

On the adaptive synchronous control of a large-scale dual-shaker platform system

Abstract: There is an ever-increasing requirement for higher power vibrating platforms to test large-scale structures. Whilst this may be achieved with a single shaker, this is an expensive option. An alternative solution is to drive a platform with two or more smaller shakers. To do this effectively, however, requires the identical amplitude and phase response of the shakers. In practice, due to manufacturing tolerances and uneven loading, this is not possible without a control system. The design and implementation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The acceleration of vibrations is incorrect. The following three components are included in the planning and construction of a multistage gear train vibration active control test platform's active control structure, control system, and signal acquisition and handling system [20].…”
Section: Simulation Design Of Active Damping System For Floating Raftmentioning
confidence: 99%
“…The acceleration of vibrations is incorrect. The following three components are included in the planning and construction of a multistage gear train vibration active control test platform's active control structure, control system, and signal acquisition and handling system [20].…”
Section: Simulation Design Of Active Damping System For Floating Raftmentioning
confidence: 99%
“…In the literature [25], the hydraulic system was modeled and adjusted through a fuzzy PID controller optimized by particle swarm optimization; the simulation showed that the fuzzy PID with particle swarm optimization was more accurate for hydraulic system synchronization control. In the literature [26], an adaptive FxLMS algorithm was used in the synchronous control of a dual-shaker system; considering the dynamic coupling between the shakers, the simulation was presented to verify the effectiveness of the control algorithm. The master-slave synchronous control strategy, as described in references [27][28][29], employs a series structure in which the slave hydraulic circuit initially follows the output signal of the main hydraulic circuit instead of tracking the desired signal from the outset [30].…”
Section: Introductionmentioning
confidence: 99%
“…From the recently published works concerning the synchronization of vibrators (Chen et al, 2016; Cieplok and Wojcik, 2020; Lyan et al, 2021; Zhang 2020; Zhang et al, 2020, 2021; Zhao et al, 2010), the dynamic model become more closely related to the actual vibrating machines including vibrating conveyor, vibrating screen, and vibrating mill, and so on. Besides, although the control synchronization (Fang et al, 2021; Fradkov et al, 2021; Huang et al, 2021; Jia et al, 2019; Li et al, 2022), multiple-frequency synchronization (Li and Chen, 2019; Zou et al, 2021), and composite synchronization (Kong and Wen, 2018) have also been investigated, the self-synchronization theory was still the most typical synchronization strategy used in engineering. With the development of synchronization theory, some scholars also paid attentions to other problems in designing vibrating machines, such as dynamic adjustment of vibration direction angle for the vibrating screen (Chen et al, 2020), and two-stage vibration isolation of vibratory shake-out conveyor (Fiebig and Wrobel, 2017).…”
Section: Introductionmentioning
confidence: 99%